The Application of the Attorney-Client Privilege to Non-Testifying Experts: Reestablishing the Boundaries Between the Attorney-Client Privilege and the Work Product Protection - Edward J. Imwinkelried (Washington University Law Quarterly, 1990)
The first part of the Article analyzes the client's direct communications with the expert, acknowledging that, at least in some circumstances, those communications should be protected absolutely under the attorney-client privilege. The balance of the Article, however, differentiates between the client's communications and the rest of the expert's information, including the expert's conclusions and reasoning process. The Article asserts that one can draw a principled distinction between the client's communications and the rest of the expert's information. The second part of the Article argues that the rest of the expert information in its own right does not qualify under the attorney-client privilege. The third and final part of the Article focuses on the admittedly close relationship between the client's communications with the expert and the rest of the expert's information. This part contends that even given the difficulty in some cases of severing the references to the communications from the balance of the expert's report, the opposition- the prosecution in our hypothetical-is entitled to discover the balance of the report.
Keywords: Confidential communications -- Lawyers; Work-product rule